Sell like a Navy Seal - Sleete, Jeff (Editor & Publisher, 2025)
[...]we didn't want to deal with the maintenance and other issues of boat ownership, so we joined a boat club. To be a member, you had to go through their boating education course run by a former Navy Seal team master chief petty officer. Small bursts of engine power are used - followed by shifting to neutral - to guide a boat into a slip gently.